ANALISA TERHADAP KEBIJAKAN PERIZINAN USAHA BERBASIS RESIKO - Habibie Hendra Carlo; Dicky Herdyawan Bachrudin; Sonny Ferra Firdaus (GEMA PUBLICA, 2021)
Investment still have important role in accelerate the economy of the countries. Lack of information concerning business operation and excessive bureaucratic procedures still become the major problem in several developing countries including Indonesia. As one of the innovation in public services, e-Government is expected to increase the quality of public services. One of the effort to increase the quality of public service in Indonesia is by enacted the Risk Based Analysis Business Licensing Process Policy. the Risk Based Analysis Business Licensing Process Policy through OSS Systems is expected integrated business licensing process that increase the quality of public services in Indonesia however the Government have to facilitate the OSS systems training for Public Servant and facilitate the socialization for the society in several region that have low Human Development Index. In the other side, the Risk Based Analysis Business Licensing Process Policy is able to become the resolution of the conflict between business actor and public servant in business licensing process.Keyword: E-Government, Pelayanan Publik, Resolusi Konflik